Inhibitory Receptor Diffusion Dynamics - Maynard, Stephanie A.; Triller, Antoine (Frontiers in Molecular Neuroscience, 2019)
The dynamic modulation of receptor diffusion-trapping at inhibitory synapses is crucial to synaptic transmission, stability and plasticity. In this review, we will outline the progression of understanding of receptor diffusion dynamics at the plasma membrane. We will discuss how regulation of reversible trapping of receptor-scaffold interactions in combination with theoretical modeling approaches can be used to quantify these chemical interactions at the postsynapse of living cells.